PENGARUH GREEN PRODUCT DAN CUSTOMER PERCEIVED VALUE TERHADAP PURCHASE INTENTION JAM TANGAN KAYU SERIBU SATOE - lufie, muhammad aluf ma’; kaihatu, thomas stefanus; effendi, laij victor (PERFORMA, 2022)
This research is done to find out The Effect of Green Products and Customer Perceived Value on Purchase Intention of Seribu Satoe Wooden Watch, this research uses quantitative approach with population that is taken from 133 respondents with purposive sampling technique with criteria of Seribu Satoe prospective consumers who have interest in Seribu Satoe wooden watch and domiciled in Surabaya, Gresik. This research uses multiple linear regression analysis method that is processed through SPSS. The data collection method is done by distributing online questionnaires through google form. The results of this research indicate that green products, customer perceived value have significant effect on purchase intention with significant value of t test result of 0.000 green product variable, and customer perceived value of 0.000, all significant value ​​are the rate of <0.05. Therefore, it can be concluded that green product variable and customer perceived value affect partially on purchase intention variable